Ovarian cancer - Ozols, Robert F.; American Cancer Society (Hamilton, Ont. ; London : B C Decker, 1999)
Ovarian Cancer provides a complete overview of the subject and features timely advice on screening, diagnosis and treatment. This volume is part of the American Cancer Society's ACS Atlas of Clinical Oncology Series.
Includes CD-ROM.
Keywords: Ovaries -- Cancer; Ovarian Neoplasms -- diagnosis; Ovarian Neoplasms -- therapy; Ovarian Neoplasms; Atlas